Endoscopic Sinus Surgery with Antrostomy Has Better Early Endoscopic Recovery in Comparison to the Ostium-Preserving Technique. (18th June 2012) - Luukkainen, Annika; Myller, Jyri; Torkkeli, Tommi; Rautiainen, Markus; Toppila-Salmi, Sanna
Abstract : Background . Endoscopic sinus surgery (ESS) is considered for chronic rhinosinusitis (CRS) after failure of conservative therapy. Objective . The aim of this study was to evaluate endoscopically ostium patency and mucosal recovery after ESS, with either maxillary sinus ostium-preserving or -enlarging techniques. Materials and Methods . Thirty patients with non-polypous CRS were enrolled. Uncinectomy-only and additional middle meatal antrostomy were randomly and single-blindly performed for each side. Pre- and postoperative endoscopic scores were semi-quantitatively determined according to findings in the ostiomeatal complex area. Adhesions, maxillary sinus mucosal swelling, secretions, and ostium obstruction were also endoscopically evaluated. In addition, symptoms were asked and computed tomography scans were taken preoperatively and 9 months postoperatively. Results . At 16 days postoperatively, a better endoscopic score and a less obstructed ostium were found with antrosomy. At 9 months postoperatively the endoscopic score improved significantly and identically with both procedures, however, obstructed ostia and sinus mucosal swelling/secretions were insignificantly more frequently found on the uncinectomy-only side. Endoscopic and radiologic findings of the maxillary sinus mucosa and ostium correlated significantly 9 months postoperatively. Conclusion . There was a good long-term mucosal recovery with both surgical procedures. In terms of early mucosal recovery and ostium patency, antrostomy might be slighly superior.